2021
DOI: 10.11591/ijere.v10i1.21006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the relationship between motivational constructs and self-regulated learning

Abstract: <span>The aim of this review was to identify the motivational constructs which were mostly associated with self-regulated learning and how these motivational constructs were related to self-regulated learning. There were 20 studies (N=8,759) met inclusion criteria for this review. In overall, the evidence of the included studies showed that motivational constructs such as self-efficacy, intrinsic goal orientation, task value, and control of learning beliefs were positively and significantly related to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
2
20
0
2
Order By: Relevance
“…It is because an SRL strategy instrument needs to incorporate the dynamic features of the behavioral factor, as displayed within the three-cycle feedback loop of Bandura (1986) social cognitive learning model and the behavioral self-regulation to execute tasks of Zimmerman and Moylan (2009) SRL model. Also, congruent with findings from previous studies about the relationship between self-efficacy and self-regulated learning strategies (Kim et al, 2015;Kaiser et al, 2020;Lim and Yeo, 2021), this study proved that English grammar SE had a significant relationship with and predictive relevance on SRL strategies in English grammar learning.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is because an SRL strategy instrument needs to incorporate the dynamic features of the behavioral factor, as displayed within the three-cycle feedback loop of Bandura (1986) social cognitive learning model and the behavioral self-regulation to execute tasks of Zimmerman and Moylan (2009) SRL model. Also, congruent with findings from previous studies about the relationship between self-efficacy and self-regulated learning strategies (Kim et al, 2015;Kaiser et al, 2020;Lim and Yeo, 2021), this study proved that English grammar SE had a significant relationship with and predictive relevance on SRL strategies in English grammar learning.…”
Section: Discussionsupporting
confidence: 90%
“…Although SRL strategies can predict SE, most studies found SE had a significant relationship with and predictive relevance on SRL (Lim and Yeo, 2021). For example, Kaiser et al (2020) reported that SE and affect explained 41.9 percent of variance on Brazilian undergraduates' SRL strategies.…”
Section: Self-efficacymentioning
confidence: 99%
“…19 More recently, we have learned that selfefficacy, intrinsic goal orientation, task value, and control of learning beliefs were the strongest positive motivational predictors of SRL. 20 Together, these studies reinforce the idea that regulatory learning is a socially driven process, and they highlight the need for us to consider assessments of SRL that tap into its motivational roots. I draw on SDT because one's quantity of motivation (e.g., towards learning) can be high, while one's quality of motivation can simultaneously be low.…”
Section: Self-determination Theory and Srlmentioning
confidence: 54%
“…Self-regulated learning can be identified through an increased ability to solve problems and assignments independently by monitoring by the teacher as a facilitator [17], [18]. The characteristics of self-regulated learning can be seen when individuals can design their learning according to the needs or goals of the individual concerned, have a strategy and carry out their learning plans, also monitor their learning progress, evaluate their learning outcomes and then compare them to specific standards [19], [20]. Independent learning can be trained through a planned learning process on science material given through a fun game approach so that students are motivated to be involved continuously without realizing it.…”
Section: Introductionmentioning
confidence: 99%